Chapter 15: Normalization of deviance in projects: its causes and implications for effective governance - Pinto, Jeffrey K.; Davis, Kate (Edward Elgar Publishing, 2023)
Organizational mistakes and accidents have a long history in practice and have been studied extensively in the engineering and organizational literature. One of the primary causes of persistent organizational error is the existence of deviance, i.e., behavior violating organizational norms. This chapter examines the behaviors and motivations of project team members in situations where deviant behaviors have been accepted and normalized as part of project operations. It discusses how normalization of deviance (NoD) manifests in terms of (1) project proposals and strategic misrepresentation, (2) client/contractor relationships, (3) planning and scheduling dynamics, and (4) workplace safety, and provides examples of NoD in practice. The chapter concludes with implications of NoD for organizational performance improvement and offers advice for how to avoid NoD situations.
Keywords: Organizational errors; Normalization of Deviance; Error; Error management; Learning; Violation; Rules